Pain in Parkinson disease: mechanistic substrates, main classification systems, and how to make sense out of them - Ciampi de Andrade, Daniel (2023)
Fil: Ciampi de Andrade, Daniel. Aalborg University. Faculty of Medicine. Department of Health Science and Technology. Center for Neuroplasticity and Pain. Dinamarca